Pembelajaran Mobile Learning dengan Bantuan SmartApp Creator pada Pembelajaran IPA Kelas VIII Materi Sistem Pernafasan - Adn, Mutiara Melati Jannatul; Rahmadhani, Kharisma Dwinda (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2022)
Digital learning media currently open opportunities to increase the variety of teaching and learning processes. Digital learning media or mobile learning is a term used to describe a learning media model that adopts the development of mobile technology as a learning medium, by presenting images, audio, and text. SmartApp Creator as one of the links to create mobile learning-based media. The purpose of this article is to describe digital media innovations in empowering 21st century critical thinking skills in science learning in junior high schools. Digital learning media developed with the help of SmartApp Creator software, then tested on seven junior high school students. This small-scale trial uses a survey and a written test. The survey was conducted to measure students' interest and motivation after trying learning media and teachers' opinions regarding digital learning media, while the written test was to measure students' understanding before and after being given digital learning media. The survey results show that the majority of students are interested and motivated after using digital learning media. The teachers stated that the digital learning media was in accordance with the aspects of learning suitability, audio-visual communication, and software engineering. The results of the written test showed a significant difference between before and after using this digital learning media. Based on these results, the developed digital learning media prototype was able to attract students' interest and motivation to learn. The results of this small-scale trial show that the media development research process can be continued into a large-scale trial to measure the effects of digital learning media on 21st century skills. Keywords: interest, mobile technology, motivation, SmartApp Creator.